2017
DOI: 10.1038/jp.2017.162
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-induced hypertension and neonatal outcomes: a systematic review and meta-analysis

Abstract: PIH was associated with reduced odds of mortality and ROP (all infants), but higher odds for BPD (<29 weeks' gestation). The paradoxical reduction in mortality may be due to survival bias and deserves further exploration in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 47 publications
12
38
1
Order By: Relevance
“…Exposure to maternal PE has been associated with a reduced rate of severe cerebral hemorrhagic lesions in preterm infants [7]. However, a recent meta-analysis of PE and pregnancy-induced hypertension and neonatal outcome failed to show any independent relationship between either prenatal exposure and prevalence of intraventricular hemorrhage (IVH) [8]. It is still unclear whether fetal exposure to maternal PE per se during early pregnancy modifies the prevalence of severe neonatal morbidities associated with preterm birth.…”
Section: Doi: 101159/000489039mentioning
confidence: 99%
“…Exposure to maternal PE has been associated with a reduced rate of severe cerebral hemorrhagic lesions in preterm infants [7]. However, a recent meta-analysis of PE and pregnancy-induced hypertension and neonatal outcome failed to show any independent relationship between either prenatal exposure and prevalence of intraventricular hemorrhage (IVH) [8]. It is still unclear whether fetal exposure to maternal PE per se during early pregnancy modifies the prevalence of severe neonatal morbidities associated with preterm birth.…”
Section: Doi: 101159/000489039mentioning
confidence: 99%
“…However emerging evidence suggests that maternal preeclampsia may represent an exception with respect to ROP risk and severity, and may even represent a natural model of ROP protection, with potential to provide novel understanding of early protective ROP mechanisms. There is considerable support for this relationship in the epidemiologic literature, including recent systematic reviews and meta-analyses [18,[172][173][174][175][176][177][178][179]. Several studies dispute this protective relationship [180][181][182], or find no association [183], however, these studies are largely limited by small sample size and lack of appropriate controls (GA, BW and presence of preterm labor) and most have suggested larger analyses are needed.…”
Section: A Novel Model Of Natural Rop Protectionmentioning
confidence: 99%
“…MSC may "reprogram" the injured tissue by delivering nanoparticles in the form of extracellular vesicles, subsequently incorporated by other cells ( figure 7). These nanoparticles, also named exosomes, are membrane vesicles, formed through the fusion of the endosomes with the plasma membrane, and can be distinguished by their size (range in size from 30 to 100 nM) (94). Exosomes are secreted by several cell types, including stem cells and are involved in the cell-to-cell communication.…”
Section: Paracrine Effectmentioning
confidence: 99%
“…Deepening the link between each mechanisms and BPD development may help the understanding of the BPD pathogenesis. A recent systematic review, examining the effects of pre-eclampsia on neonatal outcomes in premature infants, found that, although GHD did not increase the risk for BPD in the entire cohort of premature infants, it was significantly associated to BPD in infants below 29 weeks' gestation (94). However, the study was not specifically focused on BPD and it included a limited number of articles for the BPD outcome (9 studies) (94).…”
Section: Gestational Hypertension and Bpdmentioning
confidence: 99%
See 1 more Smart Citation